ANALISA PENDAPATAN PENGGUNAAN PUPUK BOKASI TERHADAP PENINGKATAN PRODUKSI TANAMAN KOL DI KELURAHAN LIABUKU KECAMATAN BUNGI KOTA BAUBAU - Hardin, Hardin (Media Agribisnis, 2019)
This study aims to: (1) To determine the amount of income obtained from farming vegetable cabbage farmer using Bokashi fertilizer in Liabuku Village, Bungi Sub-District Baubau Town; (2) To determine the feasibility value cabbage vegetable farming using Bokashi fertilizer in Liabuku Village, Bungi Sub-District Baubau Town. The population in this study were 5 people using Bokashi fertilizer on farm cabbage and five people who do not use fertilizer Bokashi, because the number of respondents who undertake entirely cabbage only 10 people, the study included a census type research. So, taken as a whole as an object of research is 10 respondents. The conclusion of this study is: (1) The total income obtained from farming vegetable cabbage farmers using Bokashi fertilizer IDR. 45.65 million, - whereas without the use of fertilizers Dokashi is IDR. 33.9 million, (2) The value of R / C-ratio derived from vegetable farming cabbage using Bokashi in Sub Liabuku is 5.72 while without using Bokashi is 3.68, so it is worth the effort; (3) The use of Bokashi fertilizer can reduce expenses in cabbage vegetable crop farming and increasing farmers' income.   Keywords: Fertilizer Bokashi, Cabbage Vegetable Revenue